LARANGAN PERCERAIAN DALAM PERSPEKTIF HUKUM ADAT LAMPUNG - Muhammad Yasir Fauzi; Agus Hermanto; Saiyah Umma Taqwa (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
The people of Lampung have a paradigm that marriage is life and death, while divorce is forbidden because it will separate the two prominent families according to custom. This study aims to examine the paradigm of the Lampung indigenous people regarding the prohibition of divorce from the perspective of maqasid sharia. This qualitative field research has a socio-philosophical approach to reviewing maqasid sharia. While the primary data is by interviewing Lampung traditional leaders and communities, the secondary data is books and articles published about the prohibition of divorce in the indigenous people of Lampung. Philosophically, the people of Lampung have a life philosophy of pill pesenggiri (self-esteem) for the sake of maintaining the sacredness of the Lampung Pepadun traditional marriage, which is carried out according to religion and custom, so that divorce becomes a disgrace because it will lower family pride. However, this does not mean that it is absolute that divorce is an emergency exit, even though it is taboo by customary law. Meanwhile, historically, this customary prohibition law has been passed down by previous ancestors, which the indigenous people of Lampung preserved to protect their descendants (hifdzu nasl).